Seasonal waves of influenza and cause-specific mortality in Germany - Bock, Christina; Kuhn, Dorothee; Schneider, Sven; Zöllner, Iris (Central European journal of medicine, 2012)
Seasonal influenza epidemics regularly lead to an increase in population-based mortality in Germany and other industrialized nations. This study aimed to investigate seasonal variations in waves of influenza and cause-specific mortality rates. We analyzed influenza case data, monthly mortality rates and environmental temperature in the state of Baden-Wuerttemberg, Germany, between 2001 and 2006 using visual methods and bivariate statistics. Peaks in overall mortality rates were associated with waves of influenza and preceded by a drop in the environmental temperature. During an influenza epidemic, many cause-specific mortality rates increased, that is to say, there were coinciding peaks for diseases of the respiratory and the circulatory system. There are several reasons which might explain the observed temporal associations between reported cases of influenza and cause-specific mortality: 1) the general physical impairment of persons with chronic diseases; 2) the combined effect of low environmental temperatures and seasonal waves of influenza; 3) the system of coding underlying disease in death certificates. Our findings point to an underestimated role of influenza in mortality in Germany.
Gesehen am 15.11.2018